HUMANISM AND CULTURAL NATIONALISM IN VIVEKANANDA: A COMPREHENSIVE ASSESSMENT - Sharma, Sudha; Khandelwal, Jayantilal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In this research paper, two important aspects of Swami Vivekananda’s thinking, humanism and cultural nationalism, have been discussed in a historical perspective. The basic foundation of Vivekananda’s ideology is the thinking of Vedanta, and in continuation thereafter, the Advaita ideology of Adi Guru Shankaracharya is considered. The ideology propounded by Shankaracharya on the basis of the thinking of the Upanishads, Swami Vivekananda propounded it as ’Practical Vedanta’ in the public interest. The deep brilliance and energy of Indian culture was present in his thinking, and along with that, cultural inclusion in his ideology was so comprehensive that Netaji Subhash Chandra Bose called him the father of cultural nationalism in India. At present, the concept of cultural nationalism is developing not only in India but in many countries of the world, which is more comprehensive than the political concept.